PEMANFAATAN TETES TEBU SEBAGAI BAHAN TAMBAH DALAM CAMPURAN BETON - Ismunandar, Harri; Mungok, Chrisna Djaya; Supriyadi, Asep (Jurnal Mahasiswa Teknik Sipil Universitas Tanjungpura, 2016)
As it grows concrete in building construction are often used as a structure and can be used for other things. In the process of mixing concrete on the ground frequently arise in the form of stirring and casting a result of a reduction in the amount of water usage to improve the quality of concrete, it is necessary to use additive (additive) as a mixture of concrete mix so that more plastic that will facilitate and speed up concrete hardening foundry. Molasses is one of the waste produced by the sugar mills. Additional material is a lot of functions, such as adding strength concrete, binding time slows to consider the price. Tests conducted on the study include compressive strength, tensile strength and modulus of elasticity sides, as well as testing the temperature after casting, hardening time test / setting time by means of Vicat, shrinkage testing using a ruler and porosity testing. For testing compressive strength, tensile strength and modulus of elasticity sides using cylindrical test specimen with a diameter of 15 cm and 30 cm high. The test specimen consists of 147 cylinders for each - each variation. This research uses seven variations, normal concrete (N), normal concrete molasses plus 0.05% (0.05% TT), normal concrete molasses plus 0.4% (TT 0.4%), normal concrete plus drops cane 1% (TT 1%) and normal concrete plastiment P121R Sika plus 0.05% (0.05% CA), normal concrete plastiment P121R Sika plus 0.4% (CA 4%), and normal concrete Sika plus plastiment P121R 1% (1% CA) Results of testing the temperature after casting temperature rise by 1-3oC. The test results hardening time / setting time can take an average time of hardening of concrete during the 280 minutes. From the test results of concrete shrinkage that occurs Â± 0.1 cm. The test results show that the porosity by using molasses can reduce porosity. Testing of compressive strength, tensile strength and modulus of elasticity sides obtained optimum value on the concrete admixture plus molasses. In the compressive strength of an increase of 4% compared to normal concrete (N), while the tensile strength divided by 16:51% increased compared to normal concrete (N), and the modulus of elasticity increased by 24% compared to normal concrete (N). Keywords : Molasses, plastiment P121R Sika, temperature, setting time, shrinkage